2016
DOI: 10.14283/jfa.2016.86
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Effect of Carers on Patients’ Risk of Adverse Healthcare Outcomes Using the Caregiver Network Score

Abstract: Background: Although caregivers are important in the management of frail, community-dwelling older adults, the influence of different caregiver network types on the risk of adverse healthcare outcomes is unknown. Objective: To examine the association between caregiver type and the caregiver network subtest of The Risk Instrument for Screening in the Community (RISC), a five point Likert scale scored from one (“can manage”) to five (“absent/liabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Younger patients and males showed higher levels of risk and complexity, probably because their severe conditions shortened their life expectancy and men have a shorter lifespan [ 21 ]. High-risk individuals generally presented increased ratios of functional impairment, consistent with previous studies [ 17 ]; however, the demand for a primary caregiver grew with the reduction in risk level, since the lack of this service could contribute to the increase in risk level, as observed in other studies [ 31 ].…”
Section: Discussionsupporting
confidence: 89%
“…Younger patients and males showed higher levels of risk and complexity, probably because their severe conditions shortened their life expectancy and men have a shorter lifespan [ 21 ]. High-risk individuals generally presented increased ratios of functional impairment, consistent with previous studies [ 17 ]; however, the demand for a primary caregiver grew with the reduction in risk level, since the lack of this service could contribute to the increase in risk level, as observed in other studies [ 31 ].…”
Section: Discussionsupporting
confidence: 89%
“…These conditions may lead to an increased burden of care (providing additional supervision and hands on care) and compound changes in cognition. Further as insufficient data were available on the characteristics of caregivers themselves, particularly no data were available on their own co-morbidities, mood, functional and cognitive status, these variables should also be examined in future research as well as the effect of different care networks (e.g., formal versus informal) and support structures available to mitigate carer burden [ 48 ]. Finally, no standardized approach to diagnosing caregiver burden was used, potentially over or underestimating prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we showed that the caregiver network's ability to cope with mental health problems can also predict institutionalization [AUC of 0.77 (95% CI:0.61-0.94)]. Again, this has been shown when the caregiver network score, a component of the RISC, has been studied alone (42). A study conducted in two French communities over 22 years concluded that the presence of informal caregivers, especially a partner, has a strong protective effect, reducing the risk of institutionalization by 40% for a person aged ≥80 (43).…”
Section: Discussionmentioning
confidence: 51%
“…older people who live with other family members and have poor social networks (few interactions with other people) are more likely to have health problems than other adults with good social networks who live alone (44). These data reinforce that a "good" social network is a protective factor for adverse events (42). The RISC also had fair predictive validity for death [AUC of 0.77 (95% CI: 0.65-0.88)].…”
Section: Discussionmentioning
confidence: 68%